Dietary Interventions to Extend Life Span and Health Span Based on Calorie Restriction - Minor, Robin K. (Oxford University Press, 2010)
The societal impact of obesity, diabetes, and other metabolic disorders continues to rise despite increasing evidence of their negative long-term consequences on health span, longevity, and aging. Unfortunately, dietary management and exercise frequently fail as remedies, underscoring the need for the development of alternative interventions to successfully treat metabolic disorders and enhance life span and health span. Using calorie restriction (CR)—which is well known to improve both health and longevity in controlled studies—as their benchmark, gerontologists are coming closer to identifying dietary and pharmacological therapies that may be applicable to aging humans. This review covers some of the more promising interventions targeted to affect pathways implicated in the aging process as well as variations on classical CR that may be better suited to human adaptation.